Performance of Rapid, Antigen-Detecting Point-of-Care Test for Suspected SARSCoV- 2 Patients Presented to the Emergency Department - Daorattanachai, Kiattichai; Benjapongvimol, Voraporn; Srivilaithon, Winchana; Subhanudh Thavaraputta (Science & Technology Asia, 2022)
Patients who present to the emergency department (ED) with SARS-CoV-2 are highly contagious. Early diagnosis is necessary to reduce the transmission of this disease. We aimed to determine the performance of a rapid, antigen-detecting point-of-care test in symptomatic patients with suspected SARS-CoV-2 infection, using rt-PCR as the reference standard. A single- centered, cross-sectional retrospective study from data registry was conducted in the ED. Patients who were 18 years or older and had symptoms that were compatible with COVID-19 infection were eligible for inclusion. All patients were tested with rapid, antigen-detecting point-of-care tests and rt-PCR in the same visit. The diagnostic performances of the test were demonstrated with sensitivity, specificity, and predictive value, including positive predictive value (PPV) and negative predictive value (NPV). In total, 703 eligible patients were included in the analysis. Of these, 120 patients infected with SARS-CoV-2 were confirmed by rt-PCR. Total prevalence was 17.07%. The rapid antigen test demonstrated high sensitivity (87.5%), very high specificity (99.8%), PPV (99.1%), and NPV (97.5%). The test demonstrated high performance in patients with high viral loads (sensitivity of 94.2 - 100% in Ct values ≤ 25). However, the test showed a decline performance in patients with higher Ct values (sensitivity of 40 – 85.7% in Ct values > 25). In conclusion, the rapid, antigen-detecting point-of-care test showed high sensitivity and very high specificity in symptomatic ED patients, as compared to rt-PCR. This test can be used as an initial screening tool to detect and guide clinical decisions for suspected COVID-19 patients who present to the ED.